The definitive guide to Jython : Python for the Java platform - Juneau, Josh (Expert's voice in software development., 2009)
"The Definitive Guide to Jython is organized for beginners as well as advanced users of the language. The book provides a general overview of the Jython language itself, but it also includes intermediate and advanced topics regarding database, web, and GUI applications; Web services/SOA; and integration, concurrency, and parallelism, to name a few"--Resource description page